Strategi Pengelolaan Risiko dalam Bongkar Muat Curah di PT. Gelora Perkasa Belawan - Hezkiel Oscar Nababan; Dafid Ginting; Suratni Ginting (Fakultas Teknik Universitas Maritim AMNI Semarang, 2025)
The dry bulk loading and unloading process at the port presents various challenges and significant risks, ranging from work safety to operational efficiency. This study aims to identify, analyze, and formulate risk management strategies in dry bulk loading and unloading activities to minimize potential losses and improve port operational performance. The methods used in this study include a qualitative approach through interviews and risk analysis as well as library studies. The results of the study indicate that the main risks in dry bulk loading and unloading include dust hazards, equipment damage, and worker safety risks. The proposed mitigation strategy involves improving the security system, regular safety training, and routine maintenance of loading and unloading equipment. It is expected that with this risk management strategy, the port can optimize the dry bulk loading and unloading process with a higher level of safety and more efficient operational costs.